2011
DOI: 10.4028/www.scientific.net/kem.471-472.851
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chitosan Loading on the Properties of Chitosan Filled Epoxidized Natural Rubber Compounds

Abstract: The study of chitosan loading onto epoxidized natural rubber compounds were prepared by incorporation of chitosan into epoxidised natural rubber matrix using a two-roll mill. The effects of chitosan loading on the curing characteristics, tensile properties and morphology of the compounds were investigated. Results indicated that slight changes in curing time (t90), and scorch time (tS2) of the compounds with the incorporation of chitosan. An increment is observed in the maximum torque, tensile modulus and duro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…involve the utilization of natural rubber or its derivatives and chitosan [8][9][10][11][12][13][14][15][16]. Of special interest to our current work, Lertwattanaseri et al [13] reported the preparation of a novel model case of bionanocomposites comprising nanofibrous chitosan bonded to the backbone of epoxidized natural rubber (ENR) via both amino and hydroxyl groups.…”
mentioning
confidence: 99%
“…involve the utilization of natural rubber or its derivatives and chitosan [8][9][10][11][12][13][14][15][16]. Of special interest to our current work, Lertwattanaseri et al [13] reported the preparation of a novel model case of bionanocomposites comprising nanofibrous chitosan bonded to the backbone of epoxidized natural rubber (ENR) via both amino and hydroxyl groups.…”
mentioning
confidence: 99%
“…Some types significantly affect rubber blends' mechanical and physical properties. Despite having minimal effect on the properties of the blend, inert fillers improve the processability of the blends and reduce their cost [7]. A significant disadvantage of natural rubber-based blends is matrix degradation, the rate of which can be influenced but not completely reversed.…”
Section: Introductionmentioning
confidence: 99%
“…Blending polymers with another polymer for improve some properties of blends as well as good thermal stability is currently one of important topics. A number of publications [1][2][3][4] deal with incorporation of hydrophilic biopolymer such as chitosan with the epoxidized natural rubber (ENR). Generally, chitosan is biocompatible and biodegradable with wide range of applications in cosmetic, pharmaceutical, medical industries and polymer electrolyte fuel cell.…”
Section: Introductionmentioning
confidence: 99%